Simulasi Getaran Sistem Diskrit Satu Derajat Kebebasan - Rizky, Vega Amalia Eka; Ganesha, Muhammad; Sukarnoto, Tono; Soeharsono, Soeharsono (Universitas Trisakti, 2019)
Equipment has been made to simulate a discrete system vibration of one degree of freedom. The aim is to obtain equipment for learning for students in the field of mechanical vibration. Vibration simulation includes free vibration and forced vibration of discrete system in one degree of freedom. The main parts of this equipment are rigid rods with mass of 2.6 kg, vibrators with mass of 3.385 kg, spring with stiffness of 3738 N/m and loading masses. A rigid rod of 0.775 m in length is supported by a hinge on one end and hung on a spring in another position. The vibrator is rotated by an electric motor and the rotation can be adjusted from 90-1600 rpm. The vibrator is mounted on a rigid object at the position of 0.285 m, 0.385 m, 0.485 m and 0.585 m from the hinge. A spring with stiffness of 3738 N/m is placed on a rigid object at the position of the hinge. The loading masses of 1.08 kg and 2.08 kg are mounted on a rigid beam in a row at the position of 0.685 m from the hinge. For the free vibration experiments, the natural frequency for each position of vibrator is searched experimentally and theoretically. It is found that the results of the two are similar. For the forced vibration experiments, graphs of vibrational responses are constructed in the frequency domain, then the resonance frequencies are compared to the natural frequency results from the free vibration experiment. Apparently the results are very close. This shows that the research equipment made is reliable and can be used as a student learning tool.